Editor’s Preface - Burford, Mark (Current Musicology, 2001)
The increased presence of jazz studies at universities and cultural insti-tutions in the United States and abroad has brought with it a recognition of how diffuse the community of those who research and write about jazz has become. Whether this "family" of jazz scholars-both in and outside of academia-is a dysfunctional one, as Ken Burns would have us believe, or simply one that exhibits the sometimes perplexing yet more often insightful idiosyncrasy of a Thelonious Monk solo is a matter of conjecture. Un-deniable, however, is the fact that at the present moment the methodolog-ical scope of jazz scholarship has expanded to an unprecedented degree.